Optimizing Mortar Mixtures with Basalt Rubble: Impacts on Compressive Strength and Chloride Penetration - Rukzon, Sumrerng; Rungruang, Suthon; Thepwong, Ronnakorn; Chaisakulkiet, Udomvit; Chindaprasirt, Prinya (Salehan Institute of Higher Education, 2024)
This research aims to establish a theoretical framework for developing binders from waste materials to reduce cement use in mortar production. It specifically examines the potential of ground basalt rubble (BS) as a supplementary binding material for partially replacing Portland cement Type 1 (OPC) in mortar mixtures. Various substitution ratios of BS, specifically 0%, 10%, 20%, 30%, and 40% by binder weight, were tested while maintaining a constant water-to-binder ratio (W/B) of 0.45. Superplasticizers (SP) were utilized to ensure consistent workability and flow of the mixtures. The SEM-EDS analysis was conducted to examine the microstructure of the cement paste, confirming the presence of calcium silicate hydrate (C-S-H) phases resulting from the pozzolanic reactions of BS. The findings showed that, at the 7-day test, replacing cement with 10% and 20% basalt rubble (BS) by weight of the binder yielded compressive strengths of 97% and 92% compared to the control (CT) mortar. In contrast, replacements of 30% and 40% BS resulted in compressive strengths of 72% and 60% of the CT mortar, respectively. Results from 28-day tests showed that replacing 10% of OPC with BS not only increased the compressive strength but also significantly decreased chloride penetration compared to the control mortar (CT). This enhancement suggests that BS can effectively replace 10%-20% of cement, with the compressive strength of the mortar ranging from 92% to 107% of that of the control. The findings accentuate the potential of using industrial by-products such as ground basalt rubble to reduce waste, alleviate environmental impacts, and promote the development of sustainable construction materials. Doi: 10.28991/CEJ-2024-010-12-013 Full Text: PDF